Peningkatan Ekonomi Masyarakat Melalui Koperasi Serba Usaha “Ribath Darul Maslahah” Di Masjid Besar Arribath Kec. Jogoroto Kabupaten Jombang - Ali Samsuri; Amrul Muttaqin (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2021)
Of the several problems based on the mapping of problems carried out at the beginning of this service activity which is the cause of the inhibition of the development of the